Respuesta :

Answer:  Choice D

[tex]f^{-1}(x) = (x-3)^2+2\\\\[/tex]

============================================================

Explanation:

First we replace f(x) with y. This is because both y and f(x) are outputs of a function.

To find the inverse, we swap x and y and solve for y like so

[tex]y = \sqrt{x-2}+3\\\\x = \sqrt{y-2}+3 \ \text{ .... swap x and y; isolate y}\\\\x-3 = \sqrt{y-2}\\\\(x-3)^2 = y-2 \ \text{ ... square both sides}\\\\(x-3)^2+2 = y\\\\y = (x-3)^2+2\\\\f^{-1}(x) = (x-3)^2+2\\\\[/tex]

Note: because the range of the original function is [tex]y \ge 3[/tex], this means the domain of the inverse is [tex]x \ge 3[/tex]. The domain and range swap roles because of the swap of x and y.

As the graph shows below, the original and its inverse are symmetrical about the mirror line y = x. One curve is the mirror image of the other over this dashed line.

Ver imagen jimthompson5910

Answer:

D

Step-by-step explanation:

let y = f(x) and rearrange making x the subject

y = [tex]\sqrt{x-2}[/tex] + 3 ( subtract 3 from both sides )

y - 3 = [tex]\sqrt{x-2}[/tex] ( square both sides )

(y - 3)² = x - 2 ( add 2 to both sides )

(y - 3)² + 2 = x

Change y back into terms of x with x = [tex]f^{-1}[/tex] (x) , then

[tex]f^{-1}[/tex] (x) = (x - 3)² + 2 → D